Perancangan Pemanfaatan Tenaga Surya untuk Penyaluran Air Bersih Bagi Pesantren Attuma’ninah Kab. Lebak, Banten - Adri Senen (Sekolah Tinggi Teknik - PLN, 2020)
Clean water is one of the most vital human needs. Indonesia, which the largest part of its territory is water, in fact is still experiencing difficulties to meet the clean water needs of its population. Based on the data from the Central Statistics Agency in 2018, the percentage of households with clean drinking water sources is 72.99%. Sajira Subdistrict in Lebak, Banten is one that is affected by severe drought. They always experience drought for 6-9 months annually. The people independently built water reservoirs from mountain water sources. Water is pumped using a water pumping machine and accommodated in reservoirs, then distributed to local residents through pipes with minimum distribution distance is 1 km from the reservoir. Due to long distance of the water distribution,many houses can’t be reached by the water. It can be solved by adding a water pump in the reservoir. So the clean water distribution, which is initially only relies on pipes and gravity, can be maximized by the thrust of the water pump. Beside the water pump, the solar panel is also added to the system as a power supply. Thus, the residents don't need to pay for electricity bill to run the pumping system.